The Analysis Of Students’ Oral Performances By Using Speaking Scoring Rubric - Cut Mawar Helmanda; Rahmatun Nisa (Jurnal Dedikasi Pendidikan, 2019)
This study entitled “The Analisys of Students’ Oral Performances by Using Speaking Soring Rubric” is written to analyze the students’ oral performances ability in speaking class by using scoring rubric and to know the lecturer’s scoring rubric used to evaluate her/his students’ speaking ability. The observation sheet helped the writer to get the data about the students’ oral performances based on the scoring rubric and the interview recorded to gain the information about the scoring rubric used by the lecturer to evaluate the students’ speaking ability. As many as 15 students of English Department of Muhammadiyah University was taken as the sample through random sampling. From observation sheet, it showed that there was one student who was in perfect category, and the rest were in good, average, and bad category. While from the interview, the lecturer used David P. Harris’ asessment rubric.